The novel "Neeli Bar" from Internal issues to External Facts - Sabir Ali, Rani; Abbas, Tahir; Iqbal Siddiqui, Wasif (sourcecoder, 2022)
The novel “Neeli Bar” brings forward the complex aspects of Pakistan Nationalism, Cultural and civilized problems. This nation flourished after 1947. Tahir Iqbal has presented the problems of refugees related to their homelessness, migration and broken values through the characters. Human Senses are stunned by the way how shadow less heinous agents sexually exploits the children. She extremely feels the pain of martyrs in Afghan war. The incident of 9/11 increases this pain. The loss of lives is shown through drones attacks. The worriers are surprised because they are only fighters who are sometimes encouraged to fight against the foreign powers and sometimes plan the suicide blasts against their near ones and damage the repute of Islam.